(untitled) (CIPEEX, 2025)
Efficient management of logistics processes in university warehouses constitutes a strategic element for ensuring the continuity of academic and administrative activities. In private higher education institutions, such processes assume even greater relevance due to budgetary constraints and the consequent need for resource optimization. Among the practices adopted to enhance inventory management, the methods of standardization, categorization, and visual control of inputs are noteworthy. The present study aimed to analyze and propose guidelines for improving inventory management in university warehouses, emphasizing the use of visual tools such as color coding and organizational methodologies, including the Kanban system and the ABC curve, with the objective of promoting greater control, traceability, and operational efficiency. This descriptive and exploratory research was based on a literature review and the analysis of practical experiences conducted in a private higher education institution. Documentary sources, case studies, and scientific articles addressing logistics practices applied to both institutional and industrial contexts were utilized. The practical experience examined consisted of the implementation of a visual color categorization system in the warehouse of the aforementioned institution. This classification system was adopted to facilitate the monitoring of the expiration dates of stored supplies. Products were marked as follows: red for items expiring in 2025, yellow for those expiring in 2026, and blue for those with an expiration date in 2027 or later. This visual systematization generated significant gains in the agility of material identification and separation, contributing to the prevention of losses resulting from expiration. When combined with standardized procedures and the use of tools such as Kanban and the ABC curve, the color categorization system enabled improved planning of purchases and replenishment based on actual demand. Furthermore, it was observed that the development and adoption of operational manuals strengthened item traceability and enhanced the accuracy of control routines. The experience described demonstrates that the integration of process management tools with visual categorization systems constitutes an effective strategy for optimizing the administration of university warehouses. The application of color coding proved to be an efficient resource for organizing and controlling inventories, fostering more assertive and sustainable decision-making. When systematized and aligned with a culture of continuous improvement, such practices contribute to institutional governance and the professionalization of resource management in private higher education institutions.